1981
DOI: 10.1128/aac.19.1.170
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of arabinosyladenine, arabinosylhypoxanthine, and arabinosyladenine 5'-monophosphate against herpes simplex virus, varicella-zoster virus, and cytomegalovirus with their effects on cellular deoxyribonucleic acid synthesis

Abstract: In a single line of human foreskin fibroblasts, minimum inhibitory concentrations (MICs) and the minimum intracellular virus inactivation concentrations (MIICs) of arabinosyladenine, arabinosylhypoxanthine, and arabinosyladenine 5'-monophosphate were assayed for a number of recent isolates of herpes simplex virus types 1 and 2 (HSV-1, HSV-2), varicella-zoster virus (VZV), and cytomegalovirus (CMV). (The term MIIC is used here to describe the selective qualitative intracellular inhibition of the virus inoculum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

1982
1982
2004
2004

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 33 publications
(25 reference statements)
2
5
0
Order By: Relevance
“…A marked reduction in number of plaques was always accompanied by a reduction in plaque size in the cultures treated with any of the drugs tested. In accord with our observation, previous studies have shown that treatment with 9-3-D-arabinofuranosyladenine or ACV results in slower development of plaques of VZV or reduction in its plaque size at concentrations below the minimum inhibitory concentration (1,6). In the present study, we noted a reduction in number of plaques only in drug-treated cultures.…”
supporting
confidence: 80%
“…A marked reduction in number of plaques was always accompanied by a reduction in plaque size in the cultures treated with any of the drugs tested. In accord with our observation, previous studies have shown that treatment with 9-3-D-arabinofuranosyladenine or ACV results in slower development of plaques of VZV or reduction in its plaque size at concentrations below the minimum inhibitory concentration (1,6). In the present study, we noted a reduction in number of plaques only in drug-treated cultures.…”
supporting
confidence: 80%
“…Our data indicate also that there is no strain-dependent difference in antiviral drug susceptibility between the KMcC and Oka strains of V-Z vaccine virus. Since our EDs are generally consistent with those of other authors who tested either lower-passaged virus (15,16,22,30) or a larger number of different strains (4,8,9,12,15,17,22,30), a general conclusion appears to be that susceptibility of V-Z virus to the antiviral compounds tested is not significantly altered by changes in passage level or strain. With respect to other strains of V-Z virus, one would expect BVDU and FIAC or ACV and Ara-A to be of comparable in vitro potency, the former two, however, being far more active than the latter two.…”
Section: Resultssupporting
confidence: 77%
“…Since there are no data suggesting that simple tissue culture passage results in the development of thymidine kinase-deficient mutants, it is not surprising that the high-passage KMcC virus and the Oka vaccine virus were no less susceptible than their low-passage counterparts were to ACV (6,15,30), BVDU (15,30), and FIAC (21). The activity of DNA polynierase was also not affected, as evidenced by the equal susceptibility of viruses of different passage levels to Ara-A (11,17), PFA (19,33), and aphidicolin (3,10,25), which specifically inhibits a-polymerase. Our data indicate also that there is no strain-dependent difference in antiviral drug susceptibility between the KMcC and Oka strains of V-Z vaccine virus.…”
Section: Resultsmentioning
confidence: 99%
“…Neplanocin C was, in general, equally cytotoxic but less potent than neplanocin A. If for each cell system (Tables 1 through 3), the lowest minimum cytotoxic concentrations were compared to the lowest minimum antiviral concentrations ( with previous findings that hypoxanthine derivatives are, as a rule, less potent antiviral agents than their adenine counterparts, i.e., hypoxanthine arabinoside versus adenine arabinoside (4,12,20), formycin B versus formycin A (13) and 9-(2,3-dihyroxypropyl)hypoxanthine versus 9-(2,3-dihydroxypropyl)adenine (9).…”
Section: Discussionmentioning
confidence: 99%